Properties of LiCo0.5Ni0.45Ag0.05O2 thin films for high storage energy capacity by Pulsed Laser Deposition. (November 2020) - Haider, Adawiya J.; Rsool, Rafid A.; Haider, Mohammed J.; Rsool, Rusul A.; Dheyab, Amer B.
Abstract: Li-rich layer-structured cathode thin films have been successfully synthesized by combustion technique and deposited by Pulsed Laser Deposition (PLD) technique to produce LCNAO Ferrimagnetism. Pulsed Nd-YAG laser with wavelength ( λ = 532 nm ) was used and for (10 ns) and energy influence (1.4 J/cm2) at different substrate temperatures (100, 200, 300) °C and O2 pressure at 10 mbar. The structure, morphology, and magnetic properties of the films were determined by XRD, FESEM, SEM, and VSM. The results, Li rich layered structure at peak (003), very smooth surface without any pinholes or cracks. The film's cross-section view on the Si substrate was used to estimate the film thickness, which was about 63.83 nm. Better crystalline features and spherical shape, average particle size of (1-12) nm could be obtained at substrate temperature of 200 °C. The result obtained at Ms (0.695) emug-1 of powder larger than LCNAO thin film (0.147) emug-1 about 5 times with natural soft loop has emerged with a very small coercive field. The equivalent circuits of the thin film was determined by EIS at substrate temperature (100) °C, with double layer capacitance, high surface area and indicated configuration of equivalent circuits and their symbols (CR(CR)(CR)(CR)) with no defects. Finally, a LiCo0.5Ni0.45Ag0.05O2 promising cathode material for LIBs because of the high theoretical capacity of 1068.5 mAhg-1. This encourages use as a small, easy-to-carry, high storage capacity in lithium batteries - Ion battery charger used in microelectronics, magnetic resonance devices, or future Electric Vehicles (EVs).